Road Traffic Accidents of the Elderly in Chile Between the Years 2008-2017: A Register-Based Descriptive Study [Siniestros de Tránsito de Las Personas Mayores en Chile Entre Los Años 2008 y 2017 Estudio Descriptivo] - Duarte-Anselmi, G (Medwave Estudios Ltda, 2020)
Objective To determine if older adults in Chile have higher rates of traffic incidents, resulting in death or injury when compared to younger adults between 2008 and 2017. Methods The databases of the National Traffic Safety Commission of the last ten years and the data of inhabitants according to the projections made by the National Statistics Institute were used. Effect measures and 95% confidence intervals were calculated. Results The elderly in Chile had 0.5 times the rate of suffering a traffic accident, 0.6 times the rate of injury, and 1.3 times the rate of dying in a traffic accident when compared against non-elderly adults. Antofagasta and Arica were the regions with the lowest and highest occurrence of death for older adults, respectively. The leading causes of traffic accidents were the imprudence of the driver and pedestrian, which presented 1.6 and 2.6 times the death rate when compared against non-elderly adults. Of the main types of traffic accidents, only when the pedestrian was hit by a vehicle, the elderly had a higher occurrence of death (rate ratio 2.4). Conclusions Older adults presented a greater vulnerability to death by traffic accidents. Substantial differences are seen across different regions. Future research should address the characteristics of the users, the strategies that could help them to have better interacti on, and promote health with a focus on road safety for older people. © 2020, Medwave Estudios Ltda. All rights reserved.